A educação física na base nacional comum curricular: interpretações de um grupo de professoras da escola pública - Mello, Camilla Maria (2020)
In 2015, a group of teachers and researchers assigned by the National Council of Education Secretaries (Consed) and by the Union of Municipal Education Directors (Undime) worked on the creation of the Common National Curricular Base (BNCC). The objective was the creation of a document that could be a guiding axis for the elaboration of pedagogical and curricular proposals, establishing guidelines in basic education for all Brazilian students. Although the decision was not unanimous, in December 2001, the National Education Council (CNE) approved the third and last version of the BNCC. In order to present the document and implement it through the development of new courses, the States and Counties started training their teachers. In the beginning of 2018, the Municipal Network of Anchieta - ES summoned by the Municipal Secretary of Education of Anchieta (Seme), began the process of continuing education in order to study the BNCC. This process of formation and implementation of the BNCC had quite different forms of interpretations and “translations” of this document by the teachers of the Network. As a teacher at the Municipal School Amarilis Fernandes Garcia, there was a sudden interest to analyze how colleagues in the area are receiving and interpreting the BNCC. This is a Professional Master's Degree, more than just a dissertation, so what matters are the “effects” of this process in teaching practice. The teachers, as well as the researcher, would constitute the PE team of that school, holding meetings for study and discussion of the BNCC. The main objective of the research was to understand how we, teachers of PE at the Amarilis Fernandes Garcia Municipal School, understood BNCC at the time of its implementation, through the Municipal Secretary. In addition, to analyze fundamentally how these interpretations (translations) of the document changed throughout our shared study process. It is our responsibility, as human beings and as teachers, to adapt our curriculum, so that they are able to guarantee knowledge that outshines common sense and emancipates its matters to transform reality.